PEMANFAATAN BARUASA UBI JALAR UNGU SEBAGAI MAKANAN SELINGAN DALAM UPAYA PERBAIKAN STATUS GIZI IBU HAMIL - Manji Lala; nurfahmi Nurfahmi (Media Gizi Pangan, 2017)
Background: The problems of Chronic energy deficiency (CED) in pregnant women in Indonesia, particularly in the province of South Sulawesi was still relatively high. One of the government's efforts in tackling the probles was local supplementary feeding.Therefore, baruasa purple sweet potato flour which is a modification of local foods typical south Sulawesi can be a healthy alternative local supplementary feeding  for pregnant women.Methods: This study  a pre-experiment conducted in the District Moncongloe Maros  in 2016. The sample size were 30 people.Results: The results showed that around  76.7% of pregnant women like the color of purple sweet potato flour. A total of 83.4% of pregnant women liked and really like the taste of baruasa purple sweet potato flour. A total of 70.0% of pregnant women liked and really like the texture of baruasa purple sweet potato flour. A total of 76.7% of pregnant women like the smell of purple sweet potato flour. An increase of 0:02 cm upper arm circumference pregnant women after taking baruasa purple sweet potato flour.Conclusions: The study suggests that pregnant women should take advantage of local food as a food supplement for pregnant women. Further research is needed to increase the protein content. Need to do further research with larger samples and longer intervention time to see the effectiveness of this purple sweet potato flour in improving the nutritional status of pregnant womenKeywords: Baruasa purple sweet potato flour, Pregnancy